TECHNOLOGY OF GENERALIZED APERTURE INGREDIENTS CODING FOR ONBOARD MEANS OF TELECOMMUNICATIONS - Рябуха, Ю. М.; Школьник, А.Ю. (Science-based technologies, 2013)
The necessity of the development of alternative methods on JPEG image compression technologies is shown. Approach justification for compression of images based on its generalized coding of coordinate-structural and line-scaling components is carried out. The method of formation of the generalized code constructions based on addition of patterns segments of a coordinate and structural components line to the basic pattern which formed on array lines code of a line-scale component is developed. The main development stages of a way of arrays coding of line-scaling component of image fragment which are represented in the form of position numbers with unequal next elements are stated. Property dimensional positional representation with unequal adjacent elements, consisting in the fact that the upper boundary of its code is the product of the accumulated bases is substantiates. Calculation of the second code component taking into account consideration of the arrays apertures lengths as position number in differential space is carried out.